HUBUNGAN PENGETAHUAN PASIEN PASCA STROKE DENGAN TINGKAT KEPATUHAN MENJALANI FISIOTERAPI DI RSU M NATSIR SOLOK SUMATERA BARAT PERIODE JANUARI – JUNI 2022 - Andi Asda Astiah; Yusmahendri Galindra; Gelfis Sananda (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2023)
Background: Adherence in carrying out physiotherapy for post-stroke patients is important, because physiotherapy is one of the ways to optimize and maximize limb function and abilities that are still left in post-stroke patients so as to reduce dependence on others. Knowledge is one of the factors that play an important role in creating obedience for a person. Methods: This research method is an observational analytic with a cross sectional approach conducted at at RSUD M Natsir, Solok City in 2022 with a total of 42 samples and filled out a questionnaire by patients to see knowledge and compliance. The analysis test used is the rho spearman test. Results: : The results of statistical tests show that there is a meaningful relationship between post-stroke patient knowledge and compliance levels at M Natsir Hospital, Solok City. From the results of the spearman rho test, a p-value of 0.002 and an r value of 0.461 were obtained so that H0 was rejected and Ha was accepted. Conclusion: Based on the results of this study, it can be concluded that there is a meaningful relationship between post-stroke patient knowledge and compliance level.